Two‐stage polybaric formation of the new enriched, pyroxene‐oikocrystic, lherzolitic shergottite, NWA 7397. (October 2014) - Howarth, Geoffrey H.; Pernet‐Fisher, John F.; Balta, J. Brian; Barry, Peter H.; Bodnar, Robert J.; Taylor, Lawrence A.
Abstract Northwest Africa (NWA) 7397 is a newly discovered, enriched, lherzolitic shergottite, the third described example of this group. This meteorite consists of two distinct textural lithologies (1) poikilitic—comprised of zoned pyroxene oikocrysts, with chadacrysts of chromite and olivine, and (2) nonpoikilitic—comprised of olivine, low‐Ca and high‐Ca pyroxene, maskelynite, and minor abundances of merrillite, spinel, ilmenite, and pyrrhotite. The constant Ti/Al ratios of pyroxene oikocrysts suggests initial crystallization of the poikilitic lithology at depth (equivalent to pressures of approximately 10 kbar), followed by crystallization of the nonpoikilitic lithology at shallower levels. Oxygen fugacity conditions become more oxidizing during crystallization ranging from fO2 conditions of approximately QFM‐2 to QFM‐0.7. Magma calculated to be in equilibrium with the major rock‐forming minerals is LREE‐enriched relative to depleted or intermediate shergottites and has flat overall profiles. Therefore, we suggest that the parental magma for NWA 7397 had sampled an enriched, oxidized, Martian geochemical source, similar to that of other enriched basaltic and olivine‐phyric shergottites. We present a polybaric formation model for the lherzolitic shergottite NWA 7397, to account for the petrologic constraints. Three successive stages in the development of NWA 7397 are discussed (1) formation of a REE‐enriched parental magma from a distinct Martian mantle reservoir; (2) magma ponding and development of a staging chamber concomitant with initial crystallization of the poikilitic lithology; and (3) magma ascent to the near surface, with entrainment of cumulates from the staging chamber and subsequent crystallization of the nonpoikilitic lithology en route to the surface.